PENGATURAN TENTANG AKSES PEKERJAAN BAGI PENYANDANG DISABILITAS - Ririe Lantari; Yanti Fristikawati (Jurnal Paradigma Hukum Pembangunan, 2019)
State have the duty to protect their citizen including people with disabilities. Persons with disabilities have their rights to live, dignity, education as well as job. The Indonesian Government has their regulation regarding people with disabilities such as Act number 39 year 1999 on Human Rights, Act number 13 year 2003 on Manpower which is stated that manpower protection aims at guaranteeing the basic rights of workers/labor and equal opportunity as well as non-discriminatory treatment on whatever basis. The Act number 8 year 2016 on Person with Disabilities, is the new law which contain some articles on the rights to work of people with disabilities. This article will explain about the regulation in Indonesia as well internationally about the access to work for people with disabilities.